Examining Challenges Associated with Numerical Cognition in Early Years Challenges Associated with Numerical Cognition in Early Years - Bayaga, Anass; Nzuza, P (Universitas Terbuka, 2022)
Ã‚Â The current research aims at examining challenges associated with numerical cognition in early years in South Africa. Guided by cognitive learning theory, the current investigation was informed by continuous quest in South Africa. The aim was to respond to unresolved challenges associated with early numerical cognition in terms of numerical cognition through semantics and textual misunderstanding in early numerical problems and concepts. Using survey design, a sample of 80 learners was chosen and tested through descriptive statistics. Data was collected using semi-structured questionnaires. It was revealed that the challenges associated with numerical cognition in early numerical problems and concepts are counting, reading numbers that contain more than one digit, difficulties with copying numbers, mathematical signs confusion, and challenges associated with manipulatives. By implication, the study highlighted that there is a severe lack of numerical literacy and competency among learners. Implying too that teachers need to pay particular attention to both semantics and textual misunderstanding